The contradiction between self-protection and self-presentation on knowledge sharing behavior - Ortiz, Jaime; Chang, Shu-Hao; Chih, Wen-Hai; Wang, Chia-Hao (Computers in human behavior, 2017)
This study decomposes information security awareness (ISA) into general information security awareness (GISA) and information security policy awareness (ISPA), to explore how these factors affect knowledge-sharing behavior. It also investigates the effects of threat appraisal and source credibility on knowledge-sharing behavior from self-protection and self-presentation perspectives. This study adopted an online questionnaire through mySurvey for data collection. This research collected and analyzed 598 valid responses by using a structural equation modeling to validate the research hypotheses. The results indicate that GISA and ISPA have significant positive effects on threat appraisal. Whereas ISPA has a significant positive effect on knowledge-sharing behavior, GISA does not. With regard to social ties, bonding social capital and bridging social capital have significant positive effects on both source credibility and knowledge-sharing behavior. Threat appraisal has a significant negative effect, and source credibility has a significant positive effect, on knowledge-sharing behavior. In addition, threat appraisal and source credibility exert partial mediation effects on ISPA, bonding social capital, bridging social capital, and knowledge-sharing behavior. •GISA and ISPA have significant effects on threat appraisal.•Bonding/bridging social capital have significant effects on source credibility.•ISPA has a significant effect on knowledge-sharing behavior.•Threat appraisal and source credibility have significant effects on knowledge-sharing behavior.•Bonding/bridging social capital have significant effects on knowledge-sharing behavior.